2015
DOI: 10.1016/j.healthplace.2014.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood walkability, deprivation and incidence of type 2 diabetes: A population-based study on 512,061 Swedish adults

Abstract: Neighborhood walkability has been associated with increased physical activity, but only a few studies have explored the association between walkability and health outcomes related to physical activity, such as type 2 diabetes. The aim of this study was to investigate the association between objectively assessed neighborhood walkability and the 4-year incidence of type 2 diabetes in a sample of 512,061 Swedish adults aged 18 years and older. Neighborhoods were defined by 408 administratively defined geographica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
65
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 78 publications
(69 citation statements)
references
References 37 publications
3
65
1
Order By: Relevance
“…In the context of walkability and diabetes, our research is the first to address this criticism by applying a propensity score-based technique to control for systematic differences in known confounders between individuals living in high-walkability versus low-walkability areas. A prior Swedish study reported an increased incidence of diabetes among Stockholm residents living in low-walkability areas, but—unlike our findings—this association was no longer significant after adjusting for household income 13. Cultural attitudes towards walking, urban development practices and cycling and transit infrastructure vary considerably between European and North American settings, which may have contributed to this difference.…”
Section: Discussioncontrasting
confidence: 95%
“…In the context of walkability and diabetes, our research is the first to address this criticism by applying a propensity score-based technique to control for systematic differences in known confounders between individuals living in high-walkability versus low-walkability areas. A prior Swedish study reported an increased incidence of diabetes among Stockholm residents living in low-walkability areas, but—unlike our findings—this association was no longer significant after adjusting for household income 13. Cultural attitudes towards walking, urban development practices and cycling and transit infrastructure vary considerably between European and North American settings, which may have contributed to this difference.…”
Section: Discussioncontrasting
confidence: 95%
“…The more than twofold risk we observed among men with a family history of diabetes, and the inverse relationship between education level and diabetes risk, are also in agreement with previous findings [25, 26]. In addition, we found that low neighbourhood SES was associated with a higher risk of type 2 diabetes, consistent with previously reported associations between neighbourhood characteristics and diabetes risk, including studies of neighbourhood deprivation and built environment in Sweden [20]. …”
Section: Discussionsupporting
confidence: 93%
“…The following were used as adjustment variables: year of the military conscription examination (modelled simultaneously as a continuous and categorical [1969-1979, 1980-1989, 1990-1997] variable); BMI (weight in kg/height in m 2 ; modelled alternatively as a continuous or categorical variable using Centers for Disease Control and Prevention [CDC] definitions for children and adolescents aged 2 to 19 years to facilitate comparability with US studies: overweight is defined as ≥85 th and <95 th percentile and obesity as ≥95 th percentile on the CDC's 2000 sex-specific BMI-for-age growth charts, which correspond to BMI ≥25.6 and <29.0 and BMI ≥29.0, respectively, for 18-year-old men [19]); family history of diabetes in a parent or sibling (yes or no, identified from medical diagnoses in the Swedish Hospital Registry from 1964-2012 and the Swedish Outpatient Registry from 2001-2012, not self-reported, thus enabling unbiased ascertainment); highest attained education level during the study period (<12, 12-14, ≥15 years); and neighbourhood socioeconomic status (SES, included because neighbourhood characteristics have been associated with type 2 diabetes [20] and with psychosocial stress [21]; comprised of an index that includes low education level, low income, unemployment and social welfare receipt, as previously described [22], and categorised as low [>1 SD below the mean], medium [within 1 SD from the mean] or high [>1 SD above the mean]).…”
Section: Methodsmentioning
confidence: 99%
“…Similar situations are repeated across the US: diabetes risk is concentrated in low-SES contexts. 2,[4][5][6] While prior work has noted the importance of environmental context for addressing disparities [4][5][6] and there are broad calls to develop place-based interventions, there is a lack of theo- 2,7 repeatedly find that these types of attributes are not strongly associated with development of diabetes. A recent study examined both objectively assessed (eg, density of food outlets per square mile) and subjectively assessed (eg, perceived availability of fresh fruits/vegetables) aspects of the built environment, and found that only the latter were predictive of incident diabetes.…”
Section: Diabetes Disparities In Contextmentioning
confidence: 99%